Isomeric Cu(I) Azolate Frameworks Showing Contrasting Electrocatalytic CO2 Reduction Selectivities and Stabilities - Zheng, Kai; Hu, Ding‐Yi; Wang, Chao; Liang, Zi‐Jun; Zhang, Xue‐Wen; Xiao, Xian‐Xian; Wu, Jun‐Xi; Zhuo, Lin‐Ling; Lin, Duo‐Yu; Zhou, Dong‐Dong; Zhang, Jie‐Peng (Small (Weinheim an der Bergstrasse, Germany), 2025)
Metal‒organic frameworks have attracted wide interest in the electrocatalytic CO2 reduction reaction (eCO2RR), but their differences of performances originated from chemical composition and stabilities are rarely concerned. Here, isomeric Cu(I) triazolate frameworks (MAF‐2Fa and MAF‐2Fb) with similar thermal/chemical stabilities but very different coordination modes are used for eCO2RR studies. MAF‐2Fa with monotypic planar dinuclear Cu(I) coordination mode achieves high selectivity for C2H4 (53%) and C2 products (70%), with almost unchanged over a wide potential window (‒1.1 to ‒1.5 V), making it among one of the best Cu‐complex electrocatalysts. In contrast, MAF‐2Fb with multiple Cu(I) coordination modes (including planar/bent dinuclear, linear mononuclear, and trigonal mononuclear ones) showed low C2/C1 products without significant differences. More interestingly, MAF‐2Fa can maintain its performance for at least 8 h, whereas MAF‐2Fb decomposed into inorganics with inferior performance after 1.5 h. The significant differences of eCO2RR selectivities and stabilities are elucidated by computational simulations and operando electrochemical tests. Two supramolecular isomers with different coordination modes are demonstrated to possess different eCO2RR selectivities and stabilities, in which the one with uniform dinuclear Cu(I) site showed higher stability and selectivity for C2, while the other one with diverse Cu(I) sites showed relative low stability and no obvious difference of C1/C2 products.